(untitled) (Journal of Preventive and Social Medicine, 2020)
Background: Having the longevity of thyroid cancer patients, any impairment in health-related quality of life (HRQOL) during the follow-up period is of great importance. Objective: The study was conducted to determine the health related quality of life of thyroid cancer patients. Material and methods: This cross sectional study was conducted among 246thyroid cancer patients. Data were collected by face-to-face interview and reviewing medical records with semi-structured questionnaire and checklist with validated scale. The subjects were purposively selected following specific selection criteria and maintaining ethical issues. Place and period of study: The study was conducted during the period from July 2018-June 2019 in two tertiary hospitals of Dhaka city: Bangabandhu Sheikh Mujib Medical University and Dhaka Medical College Hospital, Dhaka. Results: This study revealed that majority (74.4%) of respondents was female, married (72%), housewife (61.4%), rural respondent (41.1%) and had primary education (69%). Mean (± SD) age of the respondent was 37.85(±12.20) years (range 14-70 years) and mean (± SD) monthly family income was Tk.17681(±10602). Out of 246 cases, 204 (82.9%) was papillary and 42 (17.1%) was follicular carcinoma. Main presenting features were neck swelling (91.5%), swollen lymph node (41.9%), dysphonia (57.3%) and dysphagia (35.4%). Mean (± SD) of total HRQOL score was 73.7 ± 8.39. HRQOL score of students and higher educated patients were better among the respective groups (p <.001). The study showed the association of HRQOL with clinical condition of thyroid cancer patients (R2=.025). HRQOL revealed the strong prediction with education (β=-0.888, p<.05), family income (β=0.05, p<.05), marital status (β=-0.1.384, p<.05), clinical condition (β=-0.522, p<.05) and perceived stress (β=-0.632, p<.001). Conclusion: The overall HRQOL score was considerably good in this study. Timely detection, regular motivation and attending clinical condition may significantly improve the HRQOL of thyroid cancer patients JOPSOM 2019; 38(2): 1-8